Analysis of Merchandise Sales Affecting Operating Profit on CV. XYZ Snack Period 2017 – 2018 - Santi Ratna Sari; Eddy Rosidi; Darno Darno; Wulan Purnamasari; Siti Mahmudah (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
This study aims to analyze and determine the effect of sales of merchandise that affect operating profit in the 2017-2018 CV. XYZ SNACK. There are five types of merchandise sales analyzed: sales of seblak fish, sale of tofu crackers, sale of sebasi terasi, sale of cassava chips, and sale of macaroni chips. The study will analyze the positive and significant effect of merchandise sales both simultaneously (F-test, partially (T-test), determinant test for the percentage of influence simultaneously (R-2). Test aids using SPSS version 21.The test results produce a significant value and the percentage of influence that is in the F Test (Simultaneous) the significant value of (003) means that simultaneously the effect of sales of merchandise affect the operating profit. In the T test (partial) the significance value of cassava chips sales (12.53%). influence of sales of merchandise affect operating income but not all sales have a significant value, namely the sale of cassava chips on CV. XYZ SNACK period 2017-2018